1996
DOI: 10.1111/j.1365-2923.1996.tb00862.x
|View full text |Cite
|
Sign up to set email alerts
|

European medical schools and tobacco

Abstract: Following a survey in 19 European countries of the habits, attitudes and knowledge of medical students regarding tobacco, World Health Organisation European Office and the International Union against Tuberculosis and Lung Disease jointly circulated to the Deans of all European medical schools a summary of the results, including figures for mortality for smoking-related diseases in their countries and a brief questionnaire concerning faculty action on the tobacco problem. The response rate was just over 50%, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…14 The lack of training of many physicians and other health care professionals on this specific issue has been widely reported. [15][16][17][18] In many countries current medical school curricula regarding smoking cessation are inadequate and are being addressed. While this happens, practicing physicians need to be trained through continuing medical education activities.…”
Section: Discussionmentioning
confidence: 99%
“…14 The lack of training of many physicians and other health care professionals on this specific issue has been widely reported. [15][16][17][18] In many countries current medical school curricula regarding smoking cessation are inadequate and are being addressed. While this happens, practicing physicians need to be trained through continuing medical education activities.…”
Section: Discussionmentioning
confidence: 99%
“…86 The authors reported that only 8% had a specific module on tobacco, and in most medical schools tobacco was either systematically (35%) or unsystematically (55%) integrated with other teaching; 2% did not include tobacco issues. These findings generally concur with results from the survey distributed globally to medical schools.…”
Section: Extent Of Teaching About Tobacco In Medical Schoolsmentioning
confidence: 99%
“…Byla založena European Medical Association on Smoking or Health (EMASH), jejímž cílem bylo iniciovat větší zájem lékařů o problematiku kouření (21). Na základě výsledků zmíněných studií vypracovala skupina expertů při Světové zdravotnické organizaci a International Union Against Tuberculosis and Lung Diseases (IUATLD) doporučení k výuce o kouření, které zaslala děkanům lékařských fakult (22).…”
Section: Původní Práceunclassified